The Formative Assessment Action Plan: Practical Steps to More Successful Teaching and Learning - Frey, Nancy E (ASCD, 2015)
Students perform poorly on assessments primarily because they don't see the relevance of the content they are expected to master, they think they know the material but really don't, or teachers don't recognize that students aren't learning. Now there's a way you can overcome all of those challenges by using the improved formative assessment system in this breakthrough book. Two of ASCD's most popular authors, Nancy Frey and Douglas Fisher, reveal how to create a failsafe assessment system that covers all three essentials: (1) Ensure students understand the purpose of the assignment, task, or lesson, including how they will be assessed; (2) Provide students with information about their successes and needs; and (3) Capture the performance data that teachers need to guide student learning. Learn how to create purposeful lessons that tap into students' motivation and help with their goal-setting. Discover lots of different ways to determine what students understand, what is still unclear, and how to use their mistakes to determine what to teach next. Along the way, explore effective forms of oral, written, and peer feedback that improve student performance. Embedded throughout the entire book is an instructional plan that ensures this formative assessment system helps you make better decisions about what types of teaching approaches to use in your classroom.